ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN LABUHAN BATU TAHUN ANGGARAN 2011–2013 - Putri Kemala Dewi; Nurlia Hafni (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2017)
Implementation regional autonomy through fiscal decentralization scheme Labuhan Batu regency was not fully able to explore local revenue sources that the future will support the success of each region in implementing regional autonomy. Meanwhile, the data Of APBD that The absolute nature is not enough to provide adequate information on the financial performance of the region.The purpose of this research is measure the financial performance of Labuhan Batu regency measured by calculating the ratio of the independence, effectiveness ratio, efficiency ratio, the ratio of activity / harmony, growth rate and DSCR.  The results of data analysis showed local financial independence Labuhan Batu regency Fiscal Year 2011-2013 in the category of low. Effectiveness of regional finance in the category very effective in the year 2011 - 2012 and are not effective in 2013. While the financial efficiency of the region are in the category of very efficient. When viewed from the ratio of activity / compatibility expenditures in the period 2011-2012, Labuhan Batu regency still prioritizing routine expenditure than capital expenditure. As well as the growth of local revenues tend to decline and negative in 2013, Labuhan Batu regency have a chance to do a loan because it has DSCR above 250% each year.